Galileo's pendulum : from the rhythm of time to the making of matter - Newton, Roger G. (Harvard University Press, 2004)
Bored at Mass at the cathedral in Pisa, the seventeen-year-old Galileo regarded the chandelier swinging overhead and remarked to his great surprise, that the lamp took as many beats to complete an arc when hardly moving as when it was swinging widely. Galileo's Pendulum tells the story of what this observation meant, and of its profound consequences for science and technology.